Fenomena Dehumanisasi dalam Kasus Pembunuhan dan Mutilasi Sadis Dilihat Dari Persfektif Psikologi Hukum: Studi Kasus Alvi Maulana - Anes Sefta Asmita (Jurnal Riset Multidisiplin Edukasi, 2025)
Murder and mutilation are extreme crimes that occur in everyday life, as the perpetrator not only takes the victim’s life but also mutilates the victim’s body. This study examines the phenomenon of dehumanization in a murder and mutilation case committed by Alvi Maulana against his girlfriend, Tiara Angelina Saraswati. Dehumanization is a phenomenon that leads to the loss of human qualities in an individual when committing a criminal act. In addition, social conditions, economic factors, and lifestyle demands also serve as supporting factors for acts of brutal murder and mutilation, which are further discussed in this study. This research specifically focuses on an analysis from the perspective of legal psychology, emphasizing the psychological factor of dehumanization in the acts of murder and sadistic mutilation committed by Alvi Maulana. The murder and mutilation were carried out by stabbing the victim, Tiara Angelina Saraswati, in the neck from behind. After the victim had died, Alvi Maulana consciously dismembered the victim’s body into several parts and disposed of them in multiple locations, including in front of the rented room occupied by the perpetrator and the victim, as well as in another location in the Pacet area, Mojokerto. The research method employed in this study is normative legal research with a case study approach, conducted through the analysis of media documents, interviews with law enforcement officials obtained from online news reports, and relevant references on legal psychology and dehumanization theory. The findings indicate that Alvi Maulana’s actions were influenced by multiple factors that led to dehumanization, including disturbed psychological conditions and external factors such as economic pressure and lifestyle demands from the victim, which became the primary causes of dehumanization or the loss of human values within an individual.